ACCELERATING STUDENT UNDERSTANDING THROUGH THE DEVELOPMENT OF HOLOGRAPHIC LEARNING MEDIA FOR THE INNOVATION MANAGEMENT COURSE - Rochmawati, Rochmawati; Maulida, Luthfi (Jurnal Konseling Pendidikan Islam, 2026)
The transformation of education in the digital era demands innovative learning media that can strengthen students’ understanding and retention. This study developed holography-based learning media in the Innovation Management course with the aim of accelerating the comprehension of abstract concepts and enhancing students’ ability to apply theory in practice. The method used was Design-Based Research (DBR), which includes problem identification, design, implementation, testing, and refinement of the media. Data were collected through pretests, posttests, and questionnaires to assess media effectiveness. The results showed that holography-based media improved students’ understanding of fundamental innovation management concepts such as design thinking, idea generation, and innovation diffusion in a more concrete way, strengthened long-term retention through multisensory experiences, and increased students’ confidence in analyzing case studies and developing Business Model Canvas (BMC). In addition, the sharp visual quality, ease of access, and technical stability of the media supported a smooth learning process without disruption. Holography has proven to be an innovative, effective, inclusive, and relevant learning medium to prepare students for the challenges of an innovation-driven world.